Platelets kill circulating parasites of all major Plasmodium species in human malaria - Kho, S; Barber, BE; Johar, E; Andries, B; Poespoprodjo, JR; Kenangalem, E; Piera, KA; Ehmann, A; Price, RN; William, T; Woodberry, T; Foote, S; et al. (American Society of Hematology, 2018)
Platelets are understood to assist host innate immune responses against infection, although direct evidence of this function in any human disease, including malaria, is unknown. Here we characterized platelet-erythrocyte interactions by microscopy and flow cytometry in malaria patients naturally infected with Plasmodium falciparum, P. vivax, P. malariae or P. knowlesi. Blood samples from 376 participants were collected from malaria-endemic areas of Papua, Indonesia, and Sabah, Malaysia. Platelets were observed binding directly with and killing intraerythrocytic parasites of each of the Plasmodium species studied, particularly mature stages, and was greatest in P. vivax patients. Platelets preferentially bound to infected more than uninfected erythrocytes in the bloodstream. Analysis of intraerythrocytic parasites indicated the frequent occurrence of platelet-associated parasite killing, characterized by the intraerythrocytic accumulation of platelet factor-4 and terminal deoxynucleotidyl transferase dUTP nick-end labeling of parasite nuclei (PF4+TUNEL+ parasites). These PF4+TUNEL+ parasites were not associated with measures of systemic platelet activation. Importantly, patient platelet counts, infected erythrocyte-platelet complexes and platelet-associated parasite killing correlated inversely with patient parasite loads. These relationships, taken together with the frequency of platelet-associated parasite killing observed amongst the different patients and Plasmodium species, suggest that platelets may control the growth of between 5 and 60% of circulating parasites. Platelet-erythrocyte complexes comprised a major proportion of the total platelet pool in malaria patients and may therefore contribute considerably to malarial thrombocytopenia. Parasite-killing was demonstrated to be platelet factor-4-mediated in P. knowlesi culture. Collectively, our results indicate that platelets directly contribute to innate control of Plasmodium infection in human malaria.